Geographic variation in diet, prey resources and exposure to parasites and saxitoxin in Steller sea lions in the Gulf of Alaska - Hastings, Kelly K.; Rehberg, Michael J.; Crosson, Lisa M.; Bowers, Emily K.; Lefebvre, Kathi A. (Frontiers in Marine Science, 2025)
Using DNA metabarcoding, we examined diet composition, prey resources, and saxitoxin (STX) and parasite exposure in Steller sea lions (SSL) in the Gulf of Alaska in July and October 2022–2023 using 251 scat samples and 45 seawater samples. Using 12S rRNA MiFish gene metabarcoding, diet items in Prince William Sound (PWS), Cook Inlet and near Kodiak ordered by prevalence were salmon, gadids, herring, flatfishes and capelin. Using cytochrome c oxidase subunit I (COI) gene metabarcoding, pink salmon were the most prevalent item, and two cephalopods (giant Pacific octopus and magister armhook squid) were important diet components. Diet was more diverse in October (female and male data) versus July (male only data) and in Kodiak versus other regions. Region*season variation in diet included (1) in July, dominance of pink salmon in PWS versus capelin and gadids in Kodiak, (2) magister armhook squid and pollock in PWS were replaced by giant Pacific octopus and Pacific cod in Kodiak and Cook Inlet; and (3) diverse flatfishes were observed in Cook Inlet. October male diets included more flatfishes, giant Pacific octopus and cods versus more sculpins, herring and salmon for females. Prevalent genera of parasitic intestinal worms included: Anisakis spp. roundworms (range 76.7–100% among region*seasons), Diphyllobothrium spp. tapeworms (34.5–68.0%), and Pseudoterranova spp. roundworms (19.4–50.0%). Regional fish DNA in July seawater mirrored regional July SSL diet (e.g., capelin and sculpin near Kodiak and pink salmon in PWS). STX prevalence (60.8%) and concentrations were higher than previously reported, suggesting SSL in Alaska may be chronically exposed to STX at low concentrations over a wide geographic region. Mean STX concentrations ranged from 9.28–53.32 ng/g among seasons/regions (maximum = 195 ng/g). STX was highest in PWS and Southeast Alaska (SEAK) in July, still below the seafood safety regulatory limit of 800 ng/g. Diversity of fish DNA in seawater was highest in Kodiak and SEAK. STX-producing dinoflagellates (Alexandrium spp.) were highest in July seawater in SEAK and PWS, where the STX in SSL scats were highest. DNA metabarcoding of diet and seawater, coupled with STX studies, allow better monitoring of ecosystem change affecting marine top predators and of the recovery of the endangered western SSL population.